Conducting research in Radiation Oncology remotely during the COVID-19 pandemic: Coping with isolation. (September 2020) - Dhont, Jennifer; Di Tella, Marialaura; Dubois, Ludwig; Aznar, Marianne; Petit, Steven; Spałek, Mateusz; Boldrini, Luca; Franco, Pierfrancesco; Bertholet, Jenny
Highlights: 49% of 543 survey participants worked full-time from home during the COVID-19 pandemic. Perceived productivity was lower, with associated feelings of guilt. Anxiety and depressive symptoms were higher than normative values in Europe. Anxiety symptoms were negatively correlated with the number of years in research. Mental health symptoms were lower in participants with institutional health support. Abstract: Introduction: With the COVID-19 pandemic, individuals have been forced to follow strict social isolation guidelines. While crucial to control the pandemic, isolation might have a significant impact on productivity and mental health. Especially for researchers working in healthcare, the current situation is complex. We therefore carried out a survey amongst researchers in the field of radiation oncology to gain insights on the impact of social isolation and working from home and to guide future work. Materials and methods: An online survey was conducted between March 27th and April 5th, 2020. The first part contained 14 questions intended to capture an overview of the specific aspects related to research while in isolation. The second (optional) part of the questionnaire was the validated Hospital Anxiety and Depression Scale (HADS), a self-reported measure used to assess levels of anxiety and depressive symptoms. Results: From 543 survey participants, 48.8% reported to work full-time from home. The impact on perceived productivity, with 71.2% of participants feeling less productive, caused 58% of participants to feel some level of guilt. Compared to normative data, relatively high levels of anxiety and depressive symptoms were recorded for the 335 participants who filled out the HADS questionnaire. Group comparisons found the presence of a supportive institutional program as the sole factor of statistical significance in both anxiety and depressive symptom levels. People having to work full-time on location showed higher depressive symptom levels than those working from home. Anxiety scores were negatively correlated with the number of research years. Conclusion: Results of the survey showed there is a non-negligible impact on both productivity and mental health. As the radiation oncology research community was forced to work from home during the COVID-19 pandemic, lessons can be learned to face future adverse situations but also to improve work-life balance in general.